2017
DOI: 10.1117/1.jbo.22.1.016011
|View full text |Cite
|
Sign up to set email alerts
|

Test–retest reliability of the prefrontal response to affective pictures based on functional near-infrared spectroscopy

Abstract: Functional near-infrared spectroscopy (fNIRS) is being increasingly applied to affective and social neuroscience research; however, the reliability of this method is still unclear. This study aimed to evaluate the test–retest reliability of the fNIRS-based prefrontal response to emotional stimuli. Twenty-six participants viewed unpleasant and neutral pictures, and were simultaneously scanned by fNIRS in two sessions three weeks apart. The reproducibility of the prefrontal activation map was evaluated at three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 72 publications
2
11
0
Order By: Relevance
“…Global components separated by ICA were removed. Then, we applied a second-order detrend, a discrete cosine transform-based high-pass filter (0.0078 Hz) and a low-pass filter based on the hemodynamic response function (HRF) ( Huang et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Global components separated by ICA were removed. Then, we applied a second-order detrend, a discrete cosine transform-based high-pass filter (0.0078 Hz) and a low-pass filter based on the hemodynamic response function (HRF) ( Huang et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Several different software packages have been developed to assist in the pre-processing and analysis of NIRS data, but most of these are either incomplete or adapted from other neuroimaging techniques. A study by Huang et al. (2017) analysed data using NIRS_SPM toolbox (BISP KAIST, Korea), a MATLAB-based software package that was initially designed for the statistical analysis of fMRI data and adapted for NIRS.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, before NIRS can be considered for real-world applications, further research needs to examine the test–retest reliability to establish whether the outcomes are reliable over time or whether they are influenced by extraneous day-to-day factors, such as a participant’s mood or the amount of sleep they received during the prior night. Although some preliminary studies have found the test–retest reliability of NIRS in emotion processing to be acceptable at the group level for mapwise and clusterwise scales, further research is needed to gain better insight into the reliability of the method ( Huang et al. , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations